Burnout and personality factors among surgical area nurses: a cross sectional multicentre study - Velando-Soriano, Almudena; Pradas-Hernández, Laura; Membrive-Jiménez, María José; Suleiman-Martos, Nora; Romero-Béjar, Jose L.; De La Fuente-Solana, Emilia Inmaculada; Cañadas-De La Fuente, Guillermo Arturo (Frontiers in Public Health, 2024)
Objective: To determine levels of burnout among surgical area nurses in Andalusia (Spain), to identify the phase of burnout in each participant and to consider its relationship with sociodemographic, occupational variables and personality factors considered.Data Source: Data were collected by means of questionary. All nurses working in the surgical area on the date of data collection participated in the study. Sociodemographic and related to work variables were addressed in the questionnaire. Symptoms of anxiety and depression were measured using the Educational-Clinical Questionnaire: Anxiety and Depression (CECAD). Psychological personality variables were assessed using the NEO Five-Factor Inventory (NEO-FFI), adapted for a Spanish population. Burnout was measured using the Maslach Burnout Inventory (MBI).